2007
DOI: 10.1159/000111061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sevelamer and Calcium-Based Phosphate Binders on Lipid and Inflammatory Markers in Hemodialysis Patients

Abstract: Introduction: Cardiovascular disease accounts for almost half of all deaths in individuals with chronic kidney disease stage 5 despite advances in both dialysis treatment and cardiology. A combination of lipid-lowering and anti-inflammatory effects along with avoidance of hypercalcemia should be taken into account when choosing phosphorus binders for maintenance hemodialysis (MHD) patients. Methods: We examined the association of sevelamer versus calcium-based phosphorus binders with lipid profile, inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 49 publications
3
40
0
Order By: Relevance
“…Moreover, sevelamer decreases CML levels, oxidative stress, and inflammation and increases AGER1 expression. [150][151][152][153] The results of a randomized trial in patients on HD showed that sevelamer slows calcification and suppresses pentosidine accumulation. 154 Although longterm clinical studies in patients with CKD have not yet been performed, a short-term comparison of sevelamer with calcium carbonate showed that it lowered serum AGEs in patients on HD.…”
Section: Inhibition Of Gastrointestinal Absorptionmentioning
confidence: 99%
“…Moreover, sevelamer decreases CML levels, oxidative stress, and inflammation and increases AGER1 expression. [150][151][152][153] The results of a randomized trial in patients on HD showed that sevelamer slows calcification and suppresses pentosidine accumulation. 154 Although longterm clinical studies in patients with CKD have not yet been performed, a short-term comparison of sevelamer with calcium carbonate showed that it lowered serum AGEs in patients on HD.…”
Section: Inhibition Of Gastrointestinal Absorptionmentioning
confidence: 99%
“…We studied a randomly selected group of MHD patients who participated in the substudy of the Nutritional and Inflammatory Evaluation in Dialysis (NIED) Study (see the NIED Study website at http:// www.NIEDStudy.org for more details, as well as previous publications [12][13][14][15]). The original patient cohort was derived from a pool of more than 3000 MHD outpatients during 5 yr in eight DaVita long-term dialysis facilities in the South Bay Los Angeles area.…”
Section: Patient Populationmentioning
confidence: 99%
“…18,19 In hemodialysis patients, it was determined that, with the use of sevelamer, CRP, LDL and total cholesterol levels further decreased in comparison to calcium-containing phosphorus binders. 20 In cases with ESKD with a very high cardiovascular mortality due to dyslipidemia and inflammation, the use of sevelamer has been a promising treatment method for improving hyperlipidemia and inflammation. 20 Similarly in our study, in rats with renal failure, inflammation markers increased (TNF-alpha, CRP, IL-10), but the use of sevelamer decreased these markers.…”
Section: Discussionmentioning
confidence: 99%
“…20 In cases with ESKD with a very high cardiovascular mortality due to dyslipidemia and inflammation, the use of sevelamer has been a promising treatment method for improving hyperlipidemia and inflammation. 20 Similarly in our study, in rats with renal failure, inflammation markers increased (TNF-alpha, CRP, IL-10), but the use of sevelamer decreased these markers.…”
Section: Discussionmentioning
confidence: 99%